Hurricane: a Dataflow-oriented Data Service for Smart Cities Applications - Banni, Maicon; Falci, Maria Luiza; Rosseti, Isabel; de Oliveira, Daniel (Journal of Information and Data Management, 2023)
The concept of Smart Cities has gained relevance, especially in the last decade, due to the availability of data associated with cities, e.g., car traffic, public transportation, crime data, etc. The purpose of using these data is to improve the services offered to the citizens. Most of these applications manipulate spatiotemporal data. These data are processed in a dataflow that starts with the collection, integration, and aggregation and ends with visualization. This way, specialized data services for smart city applications are most welcome. However, many of the existing data services in this context, are either specific to a particular application/domain or do not consider the entire data life cycle. In this article, we present Hurricane, a dataflow-oriented data service for smart city applications. Hurricane executes multiple dataflows to gather, pre-process, integrate, and public data. Hurricane was evaluated with an application in the area of public security and results reinforced the importance of this type of data service.